Penggunaan Feed additive herbal pakan dengan dosis berbeda terhadap kinerja budidaya dan vitalitas Ikan Lele Sangkuriang (Clarias gariepinus) di PT. Imadudin Center Bima - Lasima, Wisriati; Fajrin, Muhamad (Jurnal Akuakultur Sungai dan Danau, 2026)
Catfish is one of the most popular species for aquaculture because of its strong market demand, adequate nutritional value, and relatively simple cultivation technology. Catfish is also a species that experiences a significant increase in production demand each year. In 2022, the Ministry of Marine Affairs and Fisheries (KKP) released data showing that catfish production in Indonesia reached 1.06 million tons, with a value of IDR 18.93 trillion in 2021. The increasing demand for catfish is directly proportional to the excessive use of feed in catfish farming. Overfeeding can lead to feed accumulation at the bottom of the water, resulting in decreased water quality. Poor water quality negatively affects catfish by reducing their immunity, making them more susceptible to stress, and slowing their growth. One way to improve growth and immunity in fish is by adding feed additives to their diet. Herbal feed additives offer several advantages: they are affordable, easy to obtain, environmentally friendly, enhance fish immunity, and improve feed digestibility. This study aimed to evaluate the performance and vitality of catfish given herbal feed additives at different dosages. The experiment consisted of three treatments with three replications: K (control), A (dose of 5 ml/kg feed), and B (dose of 10 ml/kg feed). The results showed that the addition of herbal feed additives at different dosages did not significantly affect survival rate, Feed Conversion Ratio (FCR), Average Daily Growth (ADG), or resistance to formalin. However, it did have a significant effect on Mean Body Weight, absolute length, and resistance to salinity. The best results were obtained in treatment B (10 ml/kg feed), which produced a Mean Body Weight (MBW) of 53.6 g, an Average Daily Growth (ADG) of 1.64 g/day, a Feed Conversion Ratio (FCR) of 1.0, an absolute length of 11.6 cm, an absolute weight gain of 103.4 g, a 100% survival rate in the formalin test, and a salinity resistance time of 179.2 minutes.